MiR‐4510 acts as a tumor suppressor in gastrointestinal stromal tumor by targeting APOC2. Issue 7 (23rd January 2020) - Chen, Yuan; Qin, Chengkun; Cui, Xianping; Geng, Wenmao; Xian, Guozhe; Wang, Zhiyi
Abstract: Dysregulation of microRNAs (miRNAs) expression has been demonstrated in gastrointestinal stromal tumor (GIST). In this study, we aimed to determine the differential miRNAs expression in GISTs and explore the functional mechanism of differential miRNAs in GIST cells. We measured differential miRNAs in six pairs of GIST tissues and matched adjacent tissues through a high‐throughput sequencing, which was confirmed in 64 pairs of GIST tissues and adjacent tissues by real‐time polymerase chain reaction. We found that miR‐4510 expression was significantly downregulated in GIST tissues compared to matched control tissues. Luciferase reporter assay identified apolipoprotein C‐II (APOC2) as a direct target of miR‐4510. Overexpression of miR‐4510 inhibited the mRNA and protein expression of APOC2. In addition, overexpression of miR‐4510 suppressed GIST cell proliferation, migration, and invasion. Overexpression of miR‐4510 also inhibited the phosphorylation of AKT and ERK1/2, reduced the expression of matrix metallopeptidase 2 (MMP2) and MMP9. APOC2 knockdown mimicked the effect of miR‐4510 overexpression. Further investigation confirmed that APOC2 was notably upregulated in GIST tissues compared to adjacent control tissues. These results suggested that miR‐4510 downregulation could promote GIST progression, including growth, invasion, and metastasis, through increasing APOC2 expression. Abstract : 1. MicroRNA‐4510 (miR‐4510) was reduced in gastrointestinal stromal tumor (GIST) tissues compared to matched control tissues. 2. Apolipoprotein C‐II (APOC2) was identified as a direct target of miR‐4510. 3. miR‐4510 overexpression inhibited GIST cell growth, migration, and invasion